2019
DOI: 10.3390/ijgi8120546
|View full text |Cite
|
Sign up to set email alerts
|

EEG & Eye Tracking User Experiments for Spatial Memory Task on Maps

Abstract: The aim of this research is to evaluate the use of ET and EEG for studying the cognitive processes of expert and novice map users and to explore these processes by comparing two types of spatial memory experiments through cognitive load measurements. The first experiment consisted of single trials and participants were instructed to study a map stimulus without any time constraints in order to draw a sketch map afterwards. According to the ET metrics (i.e., average fixation duration and the number of fixations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…We have suggested that the advantage afforded to inputs consistent with internal predictive models is caused by the brain being better able to suppress task irrelevant information (from positions other than the immediate predicted location of the ball as it moves). This is similar to neural ‘sharpening’ models and to data that suggests enhanced sensory processing for inputs that conform to expectations, and suppression for inputs that do not conform to expectations 31 33 .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We have suggested that the advantage afforded to inputs consistent with internal predictive models is caused by the brain being better able to suppress task irrelevant information (from positions other than the immediate predicted location of the ball as it moves). This is similar to neural ‘sharpening’ models and to data that suggests enhanced sensory processing for inputs that conform to expectations, and suppression for inputs that do not conform to expectations 31 33 .…”
Section: Discussionsupporting
confidence: 81%
“…Similar ideas to our suggestion of a suppression of task irrelevant information have been advanced in literature concerning how expertise modulates cortical activity—an area with clear parallels to our task (i.e., people are novices at viewing the world upside-down, and expert at viewing upright images and footage). Experts, relative to novices, show enhanced alpha power on tasks such as map reading 33 and rifle shooting 34 . Experts also show more economical cortical activations 35 and can better inhibit attentional shifts toward task-irrelevant inputs during top-down, goal-directed behaviours 36 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Çöltekin [41] integrated eye-tracking and a traditional usability assessment into map-reading research. It is worth mentioning that GIS researchers keep searching for new methods and techniques of empirical data collection, often referring to the methods already grounded in other scientific disciplines, as EEG method that can be also integrated with eye-tracking (see e.g., [59]).…”
Section: Methods Of Gaining Insight Into Map-reading and Analysismentioning
confidence: 99%
“…For instance, average fixation duration is associated with the attentional procedures, while the number of fixations per second indicates the speed of attention. Fixation duration and the number of fixations are generally inversely correlated, and higher fixation durations indicate higher processing load [3,6]. On the other hand, saccades are short (e.g., typically 30-80 ms) and voluntary eye movements between two fixations and can be visualized as scan paths.…”
Section: Introductionmentioning
confidence: 99%